Peatland bryophyte responses to increased light from black spruce removal. Issue 1 (January 2017) - Leonard, R.; Kettridge, N.; Krause, S.; Devito, K.J.; Granath, G.; Petrone, R.; Mendoza, C.; Waddington, J.M.
Abstract: The ecohydrological impact of tree‐canopy removal on moss and peat, which provide a principal carbon store, is just starting to be understood. Different mosses have contrasting contributions to carbon and water fluxes (e.g., Sphagnum fuscum, Pleurozium schreberi ) and are strongly influenced by tree‐canopy cover. Changes in tree‐canopy cover may therefore lead to long‐term shifts in species composition and associated ecohydrological function. However, the medium‐term response to such disturbance, the associated lag in this transition to a new ecohydrological and biogeochemical regime, is not understood in detail. We investigate this medium‐term (4 years) ecohydrological, biogeochemical, and species compositional response to tree‐canopy removal using a randomized plot design within a northern peatland. This is the only study to test for the influence of increased light alone. We demonstrate that changes in treatment plots 4 years after tree‐canopy removal were not significant. Notably, P. schreberi and S. fuscum remained within their respective plots post treatment, and there was no significant difference in plot resistance to evapotranspiration or carbon exchange. Results show that tree‐canopy removal alone has little impact on bryophyte ecohydrology in the short or medium‐term. This resistance to disturbance contrasts strongly with short‐term changes observed within mineral soils, suggesting that concurrent shifts in the large scale hydrology induced within such disturbances are necessary to cause rapid ecohydrological transitions. Understanding this lagged response is critical to determine the strength of medium to long‐term negative ecohydrological feedbacks within peatlands in addition to carbon and water fluxes on a decadal timescale in response to disturbance.